2010
DOI: 10.1097/01.hjh.0000388487.43460.db
|View full text |Cite
|
Sign up to set email alerts
|

Remodelling of the heart and vessels in experimental hypertension: advances in protection

Abstract: Left ventricular hypertrophy (LVH), despite its adaptive nature, increases cardiovascular morbidity and mortality. Novel approaches for protection against pathological heart remodelling are presented in this supplement. Melatonin diminishes myocardial fibrosis in rats exposed to continuous light and N-nitro-L-arginine-methyl ester (L-NAME) treatment and reduces production of endothelium-derived constricting factors in L-NAME-induced hypertension. Melatonin, because of its extraordinary antioxidant and scavengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 71 publications
(81 reference statements)
1
28
0
1
Order By: Relevance
“…Left ventricular (LV) hypertrophy, although representing an adaptation to hemodynamic overload, is associated with increased cardiovascular risk [1, 2]. The search for new approaches for the prevention or regression of LV hypertrophy in different models of pathological myocardial growth continues [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Left ventricular (LV) hypertrophy, although representing an adaptation to hemodynamic overload, is associated with increased cardiovascular risk [1, 2]. The search for new approaches for the prevention or regression of LV hypertrophy in different models of pathological myocardial growth continues [37].…”
Section: Introductionmentioning
confidence: 99%
“…This model of melatonin-deficient hypertension seems to be more physiological than pinealectomy because it reduces only nocturnal melatonin secretion and no surgery is involved [20]. Since melatonin exerts cardiovascular protection on several levels including antioxidant and scavenging actions [21–23], endothelial protection, sympatholytic effect [2428], and antiarrhythmic effects [29], it is comprehensible that a deficiency of melatonin could result in pathological alterations in circulation and target organ damage [2, 8]. Indeed, several studies with patients suffering from acute myocardial infarction with ST segment elevation indicated that deficit of melatonin could be a negative prognostic factor of the severity of infarction, subsequent remodelling, and prognosis [3033] and that melatonin supplementation may exert beneficial effects as a radical scavenger in a human model of myocardial ischemia-reperfusion damage [34, 35].…”
Section: Introductionmentioning
confidence: 99%
“…The latter is known to be on rise in the human population. Thus, prevention and successful treatment of hypertension remains of interest to both clinicians and researchers [3][4][5][6]. Thus, prevention and successful treatment of hypertension remains of interest to both clinicians and researchers [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…10 However, measurement of regression of left ventricular mass may not be sufficient for the evaluation of the effect of treatment, and an improvement in cardiac metabolism is necessary. 11 Although studies have shown regression of LVH in SHRs after treatment, 12 cardiac metabolism has not been analysed by 18 F-FDG-PET. The importance and relevance of our findings is that analysis of 18 F-FDG uptake by PET could prove useful for evaluating new treatments in the regression of LVH in preclinical studies.…”
Section: F-fdg-pet Ventricular Hypertrophy Spontaneously Hypertensimentioning
confidence: 99%